Ar-for-dir (On the Sea’s Land) - Owen Sheers (www.owensheers.co.uk/coast-one-and-all-owen-sheers-making-of-documentary/, 2016)
Ar-for-dir (On the Sea’s Land), a sequence of poems creating a lyrical journey along the southern Gower cliffs commissioned by The National Trust.